Tackling the requirements jigsaw puzzle - Albuquerque, M.; Rashid, A. (2014 IEEE 22nd International Requirements Engineering Conference (RE): Proceedings, 2014)
A key challenge during stakeholder meetings is that of presenting the requirements and conflicts to stakeholders in a way that fosters co-responsibility and co-ownership regarding the conflicts and their resolution. In this paper, we propose a jigsaw puzzle metaphor to make identified conflicts explicit as well as an associated method to utilise this metaphor during stakeholder meetings. The metaphor provides an easy to understand language for stakeholders from otherwise diverse backgrounds. It enables stakeholders to work with a well-understood concept - that of building a system from misshapen pieces. These characteristics foster communication and team work, which improve commitment of stakeholders in co-authoring of requirements and co-responsibility in conflict handling. The gamification of conflict resolution also promotes a relaxed environment, which in turn improves team cooperation and creativity. Our experience in three user studies demonstrates that the jigsaw puzzle indeed improves such co-responsibility and co-ownership when compared with typical text-based representations of requirements.